Inflammatory Markers and Risk Factors in Hypertensive Patients: A Cross-Sectional Study (Global Journal of Medical Research, 2023)
Objective To observe risk factors that hypertensive patients present in the outpatient segment from the nursing perspective care Method Cross-sectional study where essential hypertensives of legal age belonging to the hypertension program of a municipality in Bahia were included Those with cancer hepatitis HIV lupus arthritis pregnant women and chronic corticosteroid users were excluded Collected patient demographic information and cardiovascular risk factors Results Included 61 patients with a mean age of 58 11 56 women A relationship was established between age glucose IL6 LDL vitamin D ferritin waist circumference BMI BMI CRP smoking age blood pressure LDL and neutrophil lymphocyte ratio The statistical analysis evaluated predictive variables for developing hypertension and high cardiovascular risk In the cardiovascular risk stratification 09 patients had low chance one was intermediate 37 high risk and 02 very high risk
Keywords: cardiovascular risk; risk factors; arterial hypertension